New Polyphenolic Aromatic Glycoside from Bauhinia variegata L. Stem Bark - H. Bodakhe, Surendra; Ram, Alpana; S. Bodakhe, Kiran; P. Pandey, Devi (Asian Journal of Chemistry, 2010)
A new polyphenolic aromatic glycoside characterized as 2,4,8,9,10-pentahydroxy-3,7- dimethoxyanthracene-6-O-α-L-rhamnopyranoside has been isolated from stem bark of Bauhinia variegata L. The structure was established primarily on the basis of NMR spectra and chemical transformation.